1975
DOI: 10.1029/jc080i018p02677
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurement of surface temperature fluctuations induced by small amplitude surface Waves

Abstract: The magnitudes of water surface temperature fluctuations induced by surface waves of known dynamic characteristics were measured. An infrared radiometer, capable of detecting temperature changes less than 10−4 °C with response only in the 8‐ to 13‐μm spectral region, was the prime diagnostic tool. The major experimental task was to discriminate between the thermal and reflectance contributions to the wave‐induced total radiometric signal. A technique which measures the upper bound of the reflectance contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
0
12
1
Order By: Relevance
“…Attempts to repeat these experiments demonstrated the difficulties in correcting for the reflective component (1 -E)NR in Equation (3) since water reflectivity is a strong function of angle (Reid, see Witting, 1972). Chang and Wagner (1975), however, claimed to have overcome this problem and to have verified Witting's linear theory. They showed temperature fluctuations occurring with the same frequency as that of the waves.…”
Section: Wave Mm3ctsmentioning
confidence: 99%
“…Attempts to repeat these experiments demonstrated the difficulties in correcting for the reflective component (1 -E)NR in Equation (3) since water reflectivity is a strong function of angle (Reid, see Witting, 1972). Chang and Wagner (1975), however, claimed to have overcome this problem and to have verified Witting's linear theory. They showed temperature fluctuations occurring with the same frequency as that of the waves.…”
Section: Wave Mm3ctsmentioning
confidence: 99%
“…Thus, temperature modulation due to breaking can be observed because T skin inside the breaking wake area is different from T skin outside the area. Modulation of T skin by swell waves has been observed in the ocean [3], [4] and in the laboratory [5], [6]. In the ocean, Jessup and Hesany [4] (hereafter JH) found that the magnitude of the T skin modulation was of the same order as the bulk-skin temperature difference ∆T = T bulk − T skin and that the maximum T skin occurred on the forward face of the swell crest.…”
Section: Introductionmentioning
confidence: 97%
“…The theoretical work of O'Brien (1967) and Witting (1971Witting ( , 1972 motivated experimental laboratory work by Chang and Wagner (1975), who measured the magnitude of the surface temperature fluctuation induced by surface waves and found it was related to the magnitude of the heat flux. Later, Miller and Street (1978) found results in agreement with Witting's work for low wind speed, but observed departures from the theory at higher wind speeds.…”
Section: Introductionmentioning
confidence: 98%